K-shell X-ray energy and width resonances of nitrogen and oxygen atoms. (May 2015) - Sakho, I.; Sow, M.; Wagué, A.
Abstract: Energy positions and width resonances of nitrogen and oxygen atoms are reported using the Screening Constant per Unit Nuclear Charge (SCUNC) method. Calculations are performed for the 1s2s 2 2p 3 [ 5, 3 S°] n p 4 P° and for the 1s2s 2 2p 3 [ 3 D°, 3 P°] n p 4 P° core-excited autoionizing resonances of atomic nitrogen converging respectively to the 5 S° and 3 S°, and to the 3 D° and 3 P° series limits of N + and for the 1s2s 2 2p 4 [ 2, 4 P°] n p 3 P° Rydberg series converging to the 1s −1 4 P° and 1s −1 2 P° series limits of atomic oxygen. The results obtained agree very well with available high-resolution K -edge spectra of atomic nitrogen and of atomic oxygen. The present calculations provide benchmark data for X-ray spectra in connections with the modeling of astrophysical systems. Highlights: Energy and width resonances of nitrogen and oxygen atoms. Accurate results for [ 5, 3 S°, 3 D°, 3 P°] n p 4 P° series of nitrogen atom and for [ 5, 3 S°] n p 4 P° series of atomic oxygen. Very good agreements between theory and experiment. Benchmarked data provided for X-ray spectra for modeling of astrophysical systems.